Association between Nutritional Status of a Child Using Screening Tool for Assessment of Malnutrition in Paediatrics and Clinical Outcomes in Inpatients at a Tertiary Care Hospital Setting in Eastern Nepal - Dahal, Sonia; Rimal, Hemsagar; Sahani, Hira Lal; Pyakurel, Kumud (Birat Journal of Health Sciences, 2021)
Introduction: Malnutrition in children has health and physical consequences resulting in delayed physical growth and motor development, behavioral and social problems as well as susceptibility to contracting diseases.The Screening Tool for Assessment of Malnutrition in Pediatrics (STAMP) is a specially constructed tool that uses anthropometric measurements, body composition, and patient's clinical status to predict the risk of malnutrition for inpatients at admission. There is no agreement on the ideal screening tool or scales for detecting and determining the level of malnutrition in pediatric inpatients. Various studies in the pediatric population have analyzed the association of malnutrition during hospitalization with patient outcomes, but few have analyzed whether the STAMP tool in particular could be used to predict length of hospital stay and disease severity in these patients.Objectives: We studied the use of STAMP screening tools to assess the risk of malnutrition in inpatients by including a nutritional screening in the admission process and analyze the association between the risk of malnutrition and patient outcomes (length of hospital stay and severity of disease). Methodology: We conducted a prospective single-center study between May to July 2021 at a tertiary care hospital. All patients admitted to the pediatric ward aged 1 month to 15 years with a length of stay of at least 24 hours were included into the study. Data were collected about clinical, anthropometric and demographic variables for each patient including STAMP grading, length of hospital stay and severity of disease.Results: Our study suggests comparable demographic and other patient-related variables in the three categories (mild, moderate and severe) of STAMP grading (p-value >0.05). STAMP grading was not significantly associated with both length of hospital stay and severity of disease.Conclusion: The use of STAMP as a malnutrition screening tool for pediatric inpatients is not significantly associated with length of stay or severity of disease.